Investigation of Energy Values in Tender Coconut by Various Methods - MK Raghunadh, Yakkala; Suresh, Neeluri; Mujtaba Ahmed, Mohd; Ashok, Konduru; Indra reddy, A. (International Journal of Engineering and Technology, 2018)
Even in 2017 many rural areas the daily food preparation works on conventional furnaces and peat coal as the fuel. It releases lot of smoke and harmful gases. The village blacksmith work also depends on peat coal. One of the alternative fuels for conventional furnace is tender coconut fuel. The tender coconut having lot of mineral values in addition to that it having lot of fuel values. The availability of tender coconut is round the year. In most of the cases these coconuts after drinking simply dumping in the municipal waste or dumping at out cuts of the cities. By making simple process we can convert this tender coconut into good fuel. A special machine designed for process of tender coconut. A detailed analysis done on the tender coconut in two different ways. The total coconut analysis is done two ways, one is on direct coconut where as other is individual elements of the coconut analysis like shell, inner coir, outer coir and coconut husk. The calorific value of each one calculated by using the bomb calorimeter. The exhaust gases also analyzed y using exhaust gas analyzer.Â Â
Keywords: Analysis; bomb calorimeter; coconut; exhaust; Furnace.